2021
DOI: 10.14814/phy2.14785
|View full text |Cite
|
Sign up to set email alerts
|

Maternal selenium deficiency in mice promotes sex‐specific changes to urine flow and renal expression of mitochondrial proteins in adult offspring

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression. 39 Due to the key effect of mitochondrial dysfunctions induced by Se deficiencies on disease progression, the supplementation of antioxidant compounds including sodium selenite (Na 2 SeO 3 ), sodium selenate (Na 2 SeO 4 ) and Se enriched yeast (SY) has been applied to ameliorate the oxidative stress damage caused by the exposure of bisphenol A (BPA), 40 doxorubicin, 41 monosodium glutamate, 42 aluminum, 43 docetaxel (DTX), 44 sodium azide (SA) 45 and aflatoxin B1 (AFB1) 46 via the promotion of mitochondrial functions. Furthermore, the artificial selenylation modifications of polymannuronate, polysaccharides and galactomannan (GM) have been confirmed to promote neuroprotection, 47,48 antiinflammatory, 49,50 anti-tumor activity, 51,52 hepatic protection 53,54 and antiglycative activity 55 of these biopolymers via the promotion of antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression. 39 Due to the key effect of mitochondrial dysfunctions induced by Se deficiencies on disease progression, the supplementation of antioxidant compounds including sodium selenite (Na 2 SeO 3 ), sodium selenate (Na 2 SeO 4 ) and Se enriched yeast (SY) has been applied to ameliorate the oxidative stress damage caused by the exposure of bisphenol A (BPA), 40 doxorubicin, 41 monosodium glutamate, 42 aluminum, 43 docetaxel (DTX), 44 sodium azide (SA) 45 and aflatoxin B1 (AFB1) 46 via the promotion of mitochondrial functions. Furthermore, the artificial selenylation modifications of polymannuronate, polysaccharides and galactomannan (GM) have been confirmed to promote neuroprotection, 47,48 antiinflammatory, 49,50 anti-tumor activity, 51,52 hepatic protection 53,54 and antiglycative activity 55 of these biopolymers via the promotion of antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that both glucose intolerance and other disease parameters such as renal dysfunction may be occurring in this model due to impaired thyroid function [ 14 , 30 ]. Similarly, the reduced exercise performance in the current model may relate to impaired thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hofstee et al found that maternal Se deficiency in rodents induces growth restriction, with significant decreases in fetal heart and kidney size, which predispose offspring to cardiovascular and renal dysfunction in later life [ 111 ]. These authors concluded that cardiovascular alterations took place when IUGR appear and that they are probably related to the impaired thyroid dysfunction that Se deficiency offspring present by decreasing the activity of the selenoproteins DIOs [ 120 , 121 ]. Laureano-Melo et al observed that maternal Se supplementation to Wistar rats was able to program carbohydrate and lipid metabolism, endocrine homeostasis, and feeding behavior, even in the adult offspring [ 122 ].…”
Section: Metabolic Programming and Sementioning
confidence: 99%